Evaluation, Hierarchy and Selection of the best Source of Energy by using AHP, as a Proposed Solution to an Energy and Socio-economic Problem, in the case of Colombia’s Pacific Zone - Rocha, Christian Manuel Moreno; Perez, David Fernandez; Retamoza, Jesus Rodriguez; Ortega, Jorge Silva; Bohorquez, Denis Brieva; Catalan, Luis Taborda (International Journal of Energy Economics and Policy, 2022)
This research presents the process and the results to weigh and classify a set of criteria and subcriteria to be considered in Renewable Energy Planning projects for a particular area of Colombia. The implementation of electrification programs in the study area faces various obstacles, among them the inadequate selection of criteria and sub-criteria for assessing the relevance and credibility of the implemented projects, which is very important today, causing huge losses from many points of view. It is proposed to implement a multicriteria methodology (MMCM) that prioritizes criteria and subcriteria, the selected methodology is applied to the use of renewable and conventional energy sources in urban, rural,and isolated regions, one of the most used methods in the best selection process and also when making energy decisions. The Hierarchy Analysis Process (AHP) is used, the data is obtained from a survey to a group of experts with a collection and verification period of about 4 months, only to reduce inaccuracies on the developer side. This study explains the results obtained with a new multipurpose support system that helps to prioritize the most appropriate energy decision criteria and subcriteria of energy options to provide sufficient energy to meet local needs and improve living conditions. Based on the literature review, 4 criteria and 16 subcriteria were identified and submitted to review using the AHP methodology (Hierarchical Analysis Process). It can be determined that the most important criterion is the economic, followed by the social, environmental, and technical, and a hierarchy of subcriteria related to each criterion is established, establishing that for the study area the best source of energy is photovoltaic solar by communities.